Robotic Process Automation in School Administration: Exploring the Integration of RPA Solutions to Streamline Administrative Processes and Reduce Workload - Okokoyo, Isabella Ezinwa (NIU Journal of Humanities, 2024)
Robotic Process Automation (RPA) holds immense potential for revolutionizing school administration by automating repetitive tasks, streamlining processes, and enhancing operational efficiency. This paper explores the integration of RPA solutions in school administration to streamline administrative processes and reduce workload. Beginning with an overview of RPA technology and its underlying theoretical underpinnings, the paper examines the importance of administrative efficiency in educational settings and the challenges faced by school administrators. It discusses the potential benefits of RPA integration, including improved accuracy, reduced manual effort, and optimized resource allocation. The paper also addresses considerations for implementing RPA in schools, such as data security, staff training, and scalability issues. Furthermore, it recommends among others, future directions and opportunities for leveraging RPA in school administration, including emerging trends in RPA technology, potential applications for further automation, and research directions for exploring the impact of RPA on educational outcomes. Through a comprehensive evaluation of the existing systems against the proposed RPA solutions to streamline administrative processes, this paper provides insights into the transformative potential of automation technologies in enhancing administrative efficiency and effectiveness in educational institutions. Keywords: Robotic Process Automation, School Administration, Administrative Processes, Workload Reduction